Health Literacy Among Young People With Type 1 Diabetes: A Qualitative Study of Patient Involvement - Nielsen, Margit Oien; Frejlev, Hanne; Vestermark, Anette; Larsen, Liva B.; Pietraszek, Anna; Dal, Jakob; Melgaard, Dorte (Diabetes spectrum, 2025)
This qualitative study explored the challenges and knowledge gaps among Danish youth with type 1 diabetes and subsequently introduced an information program to empower these youth in their diabetes self-management. Nine young patients 18-25 years of age who were diagnosed with type 1 diabetes, living independently, or cohabiting with a partner were included. Relevant participants were invited by mail or telephone. Group interviews were conducted to uncover the specific knowledge requirements essential for improving their diabetes health literacy. Based on these interviews, four education sessions were held. The participants identified pertinent topics, including alcohol consumption, blood glucose control, educational and employment aspects, nutrition, sexuality, pregnancy, relationships, and interactions with health care professionals (HCPs). Notably, the participants expressed a preference for personalized interactions over information dissemination through digital platforms such as mobile applications. Building on this insight, we organized four sessions to provide education on the identified subjects. These sessions were designed to facilitate networking among participants and offer them the opportunity for discussion. Although invitations were extended to all individuals aged 18-25 years with type 1 diabetes ( = 52), only 13 patients and seven relatives participated. The feedback from attendees was overwhelmingly positive. Reasons for nonparticipation included forgetfulness or a reluctance to engage in group settings. Young people with type 1 diabetes appreciate personal contact with HCPs. They do not want to receive knowledge via digital apps and virtual media but instead to meet with equals. However, it remains difficult to involve them in social events. The problem of how to create contact with young people with type 1 diabetes to strengthen their health literacy remains unsolved, and there is a need for further innovative initiatives.